Clinical profile of children with renal disease admitted to a tertiary care centre in Sri Lanka - Sathiadas, M.G.; Archchana, A.; Niroshan, V. (Sri Lanka Journal of Child Health, 2021)
Introduction: In Sri Lanka, renal diseases are increasing in the adult population. Spectrum of renal disease is different in children when compared to adults. Objectives: To determine the disease burden of paediatric renal diseases, spectrum and clinical presentation. Method: A retrospective study was done using the electronic database maintained in the paediatric professorial unit, Teaching Hospital Jaffna. Data of patients admitted from January 2015 to December 2018 were analysed using the software available. Results: Renal diseases accounted to 517 (3.9%) cases of total admissions during the study period. The male: female ratio was 1:1.1. Mean age of the patients was 3.8±1.7 years. Urinary tract infection (UTI) was the most common disease (55.9%) followed by nephrotic syndrome (17.6%) and acute glomerulonephritis (13.9%). Urine culture was positive in 40% of the patients treated for UTI and imaging studies were done in 90%. Majority (94.6%) of the nephrotic syndrome were steroid responsive and renal biopsy was performed in 23%. Chronic kidney disease (3.9%) and renal tract anomalies (1.9%) contributed to the disease load as well. The overall outcome of the renal diseases indicated that majority (49.9%) were on regular follow-up and 6.1% were referred to specialised renal units. Four (0.7%) died due to renal diseases. Conclusions: Renal diseases accounted for 3.9% of total admissions during the study period. UTI was the commonest disease (55.9%) followed by nephrotic syndrome (17.6%) and acute glomerulonephritis (13.9%).
Keywords: Renal diseases; Paediatrics; Jaffna; Sri Lanka